Academic library directors’ strategic decision-making process - Lembinen, Liisi (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
Academic libraries are going through major changes and leadership of these libraries plays a vital role. In the past, academic library directors’ strategic decision-making process has been infrequently researched. This study researched academic library directors’ strategic decision-making process and resources. During this pilot project, seven LIBER member library directors from five different countries were interviewed. As a result, two main generalizations based on these interviews can be made. First, academic library directors use various resources to make strategic decisions and second, library directors are not individualists who make important decisions alone; instead, early in the decision-making process they involve their staff and library stakeholder as well as users.